Penguatan Peran Koperasi Guna Meningkatkan Kesejahteraan Anggota Primer Koperasi Polisi (Primkoppol) Pada Kepolisian Daerah Kalimanta Selatan - Ulya Nada Afa (BIMA: Jurnal Bisnis dan Manajemen, 2022)
The purpose of this study is to determine: (1) to determine the role of Primkoppol Polda South Kalimantan for the welfare of members so far. (2) to find out the steps to strengthen the role of Primkoppol Polda South Kalimantan that can be taken to improve the welfare of members. The type of research used in this research is descriptive qualitative research. Solving problems that exist in the Primary Police Cooperative (Primkoppol) of the South Kalimantan Police requires steps to manage cooperatives in a professional manner which in turn increases the role of cooperatives in other words, through strengthening the role of Primkoppol.